ARTS1 polymorphisms are associated with ankylosing spondylitis in Koreans. Issue 3 (3rd May 2009) - Choi, Chan-Bum; Kim, Tae-Hwan; Jun, Jae-Bum; Lee, Hye-Soon; Shim, Seung Cheol; Lee, Bitnara; Pope, Angela; Uddin, Mohammed; Rahman, Proton; Inman, Robert D
Abstract : Objective: To test the association between ARTS1 polymorphisms and Koreans with ankylosing spondylitis (AS). Methods: All patients and controls were Korean. 872 patients with AS fulfilling the modified New York criteria and 403 healthy controls were genotyped for five single nucleotide polymorphisms (SNPs), rs27044, rs17482078, rs10050860, rs30107 and rs2287987, known to be associated with AS in Caucasians. Results: SNPs rs27044 (p=9.37 × 10 −7 ) and rs30187 (p=7.16 × 10 −6 ) of ARTS1 were significantly associated with AS in Koreans. There was no significant association for rs17482078, rs10050860 and rs2287987. Two four-marker haplotypes were found to be associated with AS (GCCT: p=4.71×10 −7, CCCC: p=8.56×10 −6 ). Conclusions: This is first confirmation in a non-Caucasian population that genetic polymorphisms in ARTS1 are associated with AS, implicating common pathogenetic mechanisms in Korean and Caucasian patients with AS.